"More" work for nurses: the ironies of eHealth - Susanne Frennert; Lena Petersson; Gudbjörg Erlingsdottir (BMC, 2023)
Abstract Background eHealth applications are considered a technological fix that can potentially address some of the grand challenges in healthcare, including burnout among healthcare professionals, the growing burden of patients with chronic conditions, and retaining and recruiting healthcare professionals. However, as the deployment of eHealth applications in healthcare is relatively novel, there is a lack of research on how they affect the work environment of healthcare professionals. This study explores how work evolves-particularly for nurses-during the utilisation of three eHealth applications. Methods The study is a qualitative case study with an interpretive approach. The utilisation of three different eHealth applications was studied. Seventy-five healthcare professionals were interviewed, most of whom were nurses (n = 47). Interviews were transcribed verbatim and qualitative content analysis was used to analyse the text. Results Three main themes were identified: work that is ignored and overlooked; actions needed to complete visible work; and more sedentary work activities. The findings suggest that work surrounding the utilisation of eHealth applications in care practices is mostly performed by nurses. While the promise of more efficient workflows resulting from healthcare's digital transformation may be realised to different degrees, the utilisation of eHealth applications creates additional invisible labour for nurses. Conclusion We identified through our analysis that the extra work created by eHealth applications is invisible at the organisational level. Most of the invisible labour was performed by nurses, who were engaged in utilising the eHealth applications. This needs to be recognised when implementing eHealth applications in care practices.